BIM modeling for contractors - Improving model takeoffs - André Monteiro (2012)
As industry stakeholders investigate on the best uses for Building Information Modeling (BIM), its shortcomings begin to be realized, the need for modeling parameterization becomes more evident and methods to better approach these issues developed. Automatic quantity takeoff is one of the most important BIM-based features. Research conducted by the authors shows that in order to be successfully used, quantity takeoff requires specific model definition. Adapting a model for quantity takeoff, may, however, affect the design for other purposes. This paper surveys different approaches to BIM design, exploring the implications of each method on the outputs of the model, and taking in account the two most important types of takeoff for contractors: drawings and quantities.